Evaluation of newborn screening for biotinidase deficiency from southeastern region of Türkiye - Emine Göksoy (Trends in Pediatrics)
Objective: Biotinidase deficiency (BD) is an autosomal recessive inherited metabolic disorder. Biotin plays an important role as a cofactor of carboxylases. BD is categorized into two groups as profound and partial deficiency based on serum quantitative biotinidase enzyme activity (BA). Clinical manifestations are highly variable, ranging from severe metabolic acidosis to asymptomatic.